2022
DOI: 10.1371/journal.pone.0277116
|View full text |Cite
|
Sign up to set email alerts
|

Transposed-word effects when reading serially

Abstract: When asked to decide if an ungrammatical sequence of words is grammatically correct or not readers find it more difficult to do so (longer response times (RTs) and more errors) if the ungrammatical sequence is created by transposing two words from a correct sentence (e.g., the white was cat big) compared with a set of matched ungrammatical sequences for which transposing any two words could not produce a correct sentence (e.g., the white was cat slowly). Here, we provide a further exploration of transposed-wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 32 publications
(49 reference statements)
2
19
1
Order By: Relevance
“…However, this is apparently not the case. Two written language studies have reported that under serial presentation conditions transposed-word effects are observed in error rates but not in RTs 27 , 28 . So, it remains to be explained why the full pattern of transposed-word effects in both RTs and accuracy is seen with spoken words (the present study), but not with sequentially presented written words.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, this is apparently not the case. Two written language studies have reported that under serial presentation conditions transposed-word effects are observed in error rates but not in RTs 27 , 28 . So, it remains to be explained why the full pattern of transposed-word effects in both RTs and accuracy is seen with spoken words (the present study), but not with sequentially presented written words.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Mirault et al 27 tentatively suggested that the different patterns of transposed-word effects seen under parallel and serial word presentation might be due to the relative involvement of bottom-up and top-down processes. Parallel word presentation would be subject to both noisy bottom-up processing, with the noisy association of word identities to specific locations along a line of text 26 , 34 , as well as top-down sentence-level constraints imposing a syntactically correct word order 22 , 23 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations